1992
DOI: 10.3989/gya.1992.v43.i2.1182
|View full text |Cite
|
Sign up to set email alerts
|

Use and treatment of olive mill wastewater: current situation and prospects in Spain

Abstract: RESUMENUtilización y tratamiento del alpechín: situación actual y perspectivas en España.Las características de los alpechines se establecen desde el punto de vista de su capacidad contaminante y de los problemas típicos que surgen en las zonas de cultivo del olivo. También están descritas las soluciones de la administración del Estado para la prevención de la contaminación de aguas de superficie.Se detallan especialmente los puntos de acción incluidos dentro de un programa de Investigación y Desarrollo financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
13

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 5 publications
0
14
1
13
Order By: Relevance
“…Total phenolic compounds concentrations were also higher than those obtained by other authors [32][33][34]. These differences in the levels of phenolic compounds may be due to the variety and the degree of maturity of the processed olives [35] and also to the extraction techniques used. Caponio and Catalano have shown that even the temperature of the olives before and during crushing influences strongly the solubilization of phenolic compounds and consequently their amounts in OMW [36].…”
Section: Parameterscontrasting
confidence: 63%
“…Total phenolic compounds concentrations were also higher than those obtained by other authors [32][33][34]. These differences in the levels of phenolic compounds may be due to the variety and the degree of maturity of the processed olives [35] and also to the extraction techniques used. Caponio and Catalano have shown that even the temperature of the olives before and during crushing influences strongly the solubilization of phenolic compounds and consequently their amounts in OMW [36].…”
Section: Parameterscontrasting
confidence: 63%
“…Early work in this field considered, for a long time, the OOWW liming as a post-treatment of high yield in terms of organic matter and TSS removal precisely after the biological processes (Fiestas Ros de Ursinos and Borja, 1992). However, recent studies show that it is preferable to use it in the pre-treatment of these effluents.…”
Section: Resultsmentioning
confidence: 97%
“…2 l kg À1 of olives. OMW has a biochemical oxygen demand (BOD) of 35-48 g kg À1 and thus a high pollution potential (Fiestas Ros De Ursinos and Borja Padilla 1992).…”
Section: Introductionmentioning
confidence: 99%